A method for converting graphite into diamond under normal pressure

By reducing the tantalum wire treatment pressure in the HFCVD system, monodispersed tantalum atoms are deposited on a single crystal scale graphite substrate and annealed treatment, the transformation from graphite to diamond under normal pressure is achieved, and the preparation problem under high temperature and high pressure conditions in the prior art is solved, and a larger size of diamond is obtained.

CN117776173BActive Publication Date: 2025-02-28ZHEJIANG UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311754625.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-18
Publication Date
2025-02-28
Estimated Expiration
2043-12-18

Smart Images

  • Figure CN117776173B_ABST
    Figure CN117776173B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for converting graphite into diamond under normal pressure. Under relatively low pressure, monodisperse tantalum atoms are deposited on the surface of single-crystal flake graphite, and then annealing is performed to realize the conversion of graphite into diamond under normal pressure. The present invention obtains larger diamonds by using single-crystal flake graphite sheets, and provides a more feasible solution for preparing diamonds based on phase change of graphite under normal pressure. Compared with the high temperature and high pressure method, the present invention can realize the conversion of graphite into diamond under normal pressure, the process is simpler, and the production cost of diamond can be effectively reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a new method for converting graphite into diamond under normal pressure. Background Art

[0002] Due to its unique structure, diamond has excellent properties such as high hardness, low thermal expansion coefficient, high electron mobility, good corrosion resistance, good wear resistance, high temperature resistance and stable thermal conductivity. It is widely used in electronic devices, industrial processing, biosensors, electrochemistry and other fields.

[0003] Diamond resources in nature are very limited, while graphite is a mineral resource with abundant reserves. Therefore, graphite is often selected as the main raw material for artificial synthesis of diamond. At present, the industry usually uses high temperature and high pressure method and detonation method to transform graphite into diamond. The high temperature and high pressure method is to apply a high temperature and high pressure environment to the graphite precursor so that the carbon atoms in the graphite are recombined into the structure of diamond. The detonation method uses the energy generated by high explosives at the moment of explosion to act on graphite in the form of a very strong shock wave and can reach the pressure and temperature required for diamond formation in a short time, so that graphite is transformed into diamond. The production conditions of these two methods are extremely harsh. The temperature conditions required for phase change are as high as several thousand degrees Celsius, and the pressure conditions are as high as several thousand megapascals or even higher. The preparation cost is high and the energy consumption is large. Therefore, it is of great value to develop new methods for preparing diamond based on graphite.

[0004] The inventor deposited tantalum atoms escaping from tantalum wires in a hot wire chemical vapor deposition system on a pressed graphite sheet at a higher power in the early stage, and obtained diamonds with a size of about 2-3nm (see authorized patent ZL202210305804.7). However, the higher tantalum wire processing power (600-2400W) and longer processing time (30-180min) will form a large amount of TaC on the pressed graphite sheet, thereby reducing the number of monodisperse tantalum atoms and limiting the occurrence of phase change. Subsequently, by reducing the tantalum wire processing power (400W) and reducing the tantalum wire processing time (5-30min), the tantalum atom deposition process and annealing process were optimized, effectively inhibiting the formation of TaC on the graphite sheet, thereby obtaining more diamonds in the pressed graphite sheet (see accepted patent CN202310059001.2). The polycrystalline graphite flakes used in the above patents are small in size (particle size is 1 μm), which limits the size of diamonds formed by phase transformation, while single-crystalline flake graphite has better crystallinity, more ordered structure and larger size (particle size is 5 μm). In addition, changes in air pressure in the vacuum system will cause changes in the gas flow in the cavity, and the reduction in deposition pressure will cause more tantalum atoms to be deposited on the graphite flakes, which may be more conducive to the transformation of graphite to diamond, but neither of the above patents has studied lower deposition pressures. Therefore, this patent uses single-crystalline flake graphite as a substrate, and further reduces the deposition pressure during the tantalum wire processing process to obtain an appropriate amount of monodisperse tantalum atoms, promote the transformation of graphite to diamond under normal pressure, and obtain larger diamonds. Summary of the invention

[0005] The purpose of the present invention is to provide a new method for converting graphite into diamond under normal pressure. The present invention utilizes an HFCVD system to reduce the processing pressure of tantalum wire at a relatively low power, deposits the monodisperse tantalum atoms escaped from the metal tantalum wire onto the surface of a single crystal flake graphite substrate, and then performs an annealing treatment, thereby realizing the conversion of graphite into diamond under normal pressure.

[0006] The present invention adopts the following technical solution:

[0007] The present invention provides a method for converting graphite into diamond under normal pressure, the method comprising the following steps:

[0008] S1: In a hot wire chemical vapor deposition device, a tantalum wire tooling is used, a single crystal flake graphite sheet is placed in the cavity of the hot wire chemical vapor deposition device (directly below the tantalum wire) to perform tantalum deposition, and a graphite sheet treated with tantalum wire is obtained;

[0009] The tantalum deposition operation is: treating for 5 to 30 minutes (preferably 15 minutes) under the conditions of chamber pressure of 2.0 to 3.0 kPa (preferably 3.0 kPa), hot wire power of 300 to 800 W (preferably 400 W), and hydrogen flow rate of 50 to 300 sccm (preferably 200 sccm), and then reducing the power to 0 at a rate of 0.2 to 2 V / min (preferably 0.5 V / min) in a hydrogen atmosphere;

[0010] S2: The graphite sheet treated with tantalum wire described in step S2 is sealed in a vacuum quartz tube and annealed in a muffle furnace at 700-1100° C. (preferably 900° C.) for 15-120 min (preferably 30 min) to obtain diamond on the graphite sheet.

[0011] In one embodiment of the present invention, the single crystal flake graphite sheet is made by pressing single crystal flake graphite powder. Specifically, the pressure of the pressing is 30 MPa and the time is 2 min. The diameter of the obtained single crystal flake graphite sheet is 13 mm and the thickness is 1 mm. In one embodiment of the present invention, the particle size of the single crystal flake graphite powder is 5 μm.

[0012] After the sheeting is completed, the surface of the graphite sheet is cleaned with ethanol, dried with a nitrogen gun, and then placed in a hot wire chemical vapor deposition equipment.

[0013] During the tantalum deposition process, there is no need to pass a carbon source into the chamber. Chemical vapor deposition is not performed, but the tantalum wire in the equipment is used as a heat source and tantalum source.

[0014] The hot wire chemical vapor deposition equipment of the present invention was purchased from Shanghai Jiaoyou Diamond Coating Company, and the model number is JUHFCVD001.

[0015] The present invention particularly recommends that the method comprises the following steps:

[0016] S1: In a hot wire chemical vapor deposition device, a tantalum wire tooling is used, a single crystal flake graphite sheet is placed in the cavity of the hot wire chemical vapor deposition device for tantalum deposition, and a graphite sheet treated with tantalum wire is obtained;

[0017] The tantalum deposition operation is: processing for 15 minutes under the conditions of chamber pressure of 3.0 kPa, hot wire power of 400 W, and hydrogen flow rate of 200 sccm, and then reducing the power to 0 at a rate of 0.5 V / min in a hydrogen atmosphere;

[0018] S2: The graphite sheet treated with the tantalum wire described in step S2 is sealed in a vacuum quartz tube and annealed in a muffle furnace at 900° C. for 30 minutes to obtain diamond on the graphite sheet.

[0019] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) Compared with the currently commonly used high temperature and high pressure phase change process of converting graphite into diamond, this method can be realized at normal pressure and the phase change temperature is lower. (2) This method has low equipment requirements, low cost, simple process and easy operation; (3) Compared with the inventor's previous process of converting graphite into diamond at normal pressure (see patent 202310059001.2), the present invention obtains larger diamonds by using single crystal flake graphite sheets, which provides a more feasible solution for preparing diamonds based on phase change of graphite at normal pressure. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a scanning electron microscope (SEM) image of intrinsic graphite.

[0021] Figure 2 This is a transmission electron microscope (TEM) image of the intrinsic graphite substrate.

[0022] Figure 3 SEM image of Example 1 (Tantalum wire treatment gas pressure 2.0kPa-1100℃ annealing).

[0023] Figure 4 TEM image of Example 1 (Tantalum wire treated with gas pressure 2.0 kPa-1100°C annealing).

[0024] Figure 5 SEM image of Example 2 (Tantalum wire treated with gas pressure 2.5 kPa-1100°C annealing).

[0025] Figure 6 TEM image of Example 2 (Tantalum wire treated with gas pressure 2.5 kPa-1100°C annealing).

[0026] Figure 7 SEM image of Example 3 (Tantalum wire treated with gas pressure 3.0 kPa-1100°C annealing).

[0027] Figure 8 TEM image of Example 3 (Tantalum wire treated with gas pressure 3.0 kPa-1100°C annealing).

[0028] Fig. 9 SEM image of Example 4 (Tantalum wire treated with gas pressure 2.5 kPa-700°C annealing).

[0029] Fig.10 TEM image of Example 4 (Tantalum wire treated with gas pressure 2.5 kPa-700°C annealing).

[0030] Fig.11 SEM image of Example 5 (Tantalum wire treated with gas pressure 2.5 kPa-900°C annealing).

[0031] Fig.12 TEM image of Example 5 (Tantalum wire treated with gas pressure 2.5 kPa-900°C annealing).

[0032] Fig.13 SEM image of comparative example 1 (polycrystalline graphite sheet-tantalum wire treated with gas pressure 3.0 kPa-1100°C annealing).

[0033] Fig.14 TEM image of Comparative Example 1 (polycrystalline graphite sheet-tantalum wire treated with gas pressure 3.0 kPa-1100°C annealing). DETAILED DESCRIPTION

[0034] The present invention is further described below by means of specific embodiments, but the protection scope of the present invention is not limited thereto.

[0035] Example 1

[0036] (1) Single crystal flake graphite powder (particle size of 5 μm) was placed in a tablet press (manufactured by Tianjin Botian Shengda Technology Development Co., Ltd., model FW-4A, pressed at a pressure of 30 MPa for 2 min) and pressed into graphite sheets. The surface of the graphite sheet was cleaned with ethanol, and the surface was dried by a nitrogen gun to prepare a graphite sheet.

[0037] (2) The tantalum wire is tooled in the form of a double spiral. The graphite sheet prepared in step (1) is placed in a hot wire chemical vapor deposition (HFCVD) device, the chamber pressure is adjusted to be stable at 2.0 kPa, the power is 400 W, and the hydrogen flow rate is 200 sccm. After processing for 15 minutes, the power is reduced to 0 at a rate of 0.5 V / min in a hydrogen atmosphere to complete the Ta deposition process.

[0038] (3) placing the graphite sheet treated in step (2) into a quartz tube and sealing the tube, evacuating the quartz tube while sealing the tube to ensure that the quartz tube is in a near-vacuum state, placing the sealed quartz tube (with the sample inside) into a muffle furnace at 1100° C., taking out the sample after annealing for 30 minutes, and completing the annealing process.

[0039] Field emission scanning electron microscopy (FESEM) and high resolution transmission electron microscopy (HRTEM) were used to observe the composition of the samples after the experiment.

[0040] Figure 1 This is the SEM picture of the intrinsic graphite substrate. The surface is locally flat, and wrinkles appear at the junction.

[0041] Figure 2 This is the TEM image of the intrinsic graphite substrate. SAED-a mainly shows the diffraction information of graphite (002), (100) and (110) crystal planes, and the angle between the (100) crystal planes is 60°.

[0042] Figure 3 This is the SEM picture of Example 1. After annealing, there are many nanoparticles on the surface of the sample with a size of 10-50nm.

[0043] Figure 4 This is the TEM image of Example 1. From the low-magnification image (a), it can be seen that amorphous carbon spheres exist on the thin area of ​​the sample. SAED-a mainly contains diffraction rings of the (100), (110) and (112) crystal planes of graphite and diffraction points of the (111) plane of diamond. Figure (b) shows a high-magnification image of the amorphous carbon sphere. There is an area with obvious lattice fringes inside the amorphous carbon sphere. The fringes with interplanar spacing are 0.202, 0.178, and 0.101nm, corresponding to the (111), (200) and (222) crystal planes of diamond, respectively, and the angle between the (111) and (200) planes is 54°, which meets the standard crystal plane angle of cubic diamond. The previous analysis shows that there are diamond particles with a size of about 25×15nm in the sample. Compared with the 5-15nm diamonds obtained in the previous patent, the size of the diamonds obtained in this patent is significantly increased.

[0044] Example 2

[0045] (1) Single crystal flake graphite powder (particle size of 5 μm) was placed in a tablet press (manufactured by Tianjin Botian Shengda Technology Development Co., Ltd., model FW-4A, pressed at a pressure of 30 MPa for 2 min) and pressed into graphite sheets. The surface of the graphite sheet was cleaned with an ethanol solution, and the surface was dried by a nitrogen gun to prepare a graphite sheet.

[0046] (2) The tantalum wire is tooled in the form of a double spiral. The graphite sheet prepared in step (1) is placed in a hot wire chemical vapor deposition (HFCVD) device, the chamber pressure is adjusted to be stable at 2.5 kPa, the power is 400 W, and the hydrogen flow rate is 200 sccm. After processing for 15 minutes, the power is reduced to 0 at a rate of 0.5 V / min in a hydrogen atmosphere to complete the Ta deposition process.

[0047] (3) placing the graphite sheet treated in step (2) into a quartz tube and sealing the tube, evacuating the quartz tube while sealing the tube to ensure that the quartz tube is in a near-vacuum state, placing the sealed quartz tube (with the sample inside) into a muffle furnace at 1100° C., taking out the sample after annealing for 30 minutes, and completing the annealing process.

[0048] Field emission scanning electron microscopy (FESEM) and high resolution transmission electron microscopy (HRTEM) were used to observe the composition of the samples after the experiment.

[0049] Figure 5This is the SEM picture of Example 2. After annealing, the nanoparticles on the surface of the sample are larger in size and less in number than those in the sample treated with Ta wire at a pressure of 2.0 kPa (Example 1).

[0050] Figure 6 This is the TEM image of Example 2. From the low-magnification image (a), it can be seen that there are amorphous carbon spheres containing black nanoparticles inside the thin area of ​​the sample. SAED-a mainly contains diffraction rings of the (100), (110) and (201) crystal planes of graphite and diffraction points of the (111) plane of diamond. Figure (b) shows a high-magnification image of the amorphous carbon sphere, and particles 1 and 2 exist inside the amorphous carbon sphere. The enlarged image b-1 of particle 1 shows that there are lattice fringes with a crystal plane spacing of 0.207nm inside the particle, which is consistent with the crystal plane spacing of the cubic diamond (111) plane. The enlarged image b-2 of particle 2 shows that there are lattice fringes with crystal plane spacings of 0.300nm and 0.213nm inside the particle, corresponding to the (110) and (200) crystal planes of diamond, respectively, and the angle between the (110) and (200) planes is 42°. The previous analysis shows that diamond particles with a size greater than 25nm were obtained in the sample. Compared with the 5-15nm diamonds obtained in the previous patents, the diamonds obtained in this patent are larger in size.

[0051] Example 3

[0052] (1) Single crystal flake graphite powder (particle size of 5 μm) was placed in a tablet press (manufactured by Tianjin Botian Shengda Technology Development Co., Ltd., model FW-4A, pressed at a pressure of 30 MPa for 2 min) and pressed into graphite sheets. The surface of the graphite sheet was cleaned with an ethanol solution, and the surface was dried by a nitrogen gun to prepare a graphite sheet.

[0053] (2) The tantalum wire is tooled in the form of a double spiral. The graphite sheet prepared in step (1) is placed in a hot wire chemical vapor deposition (HFCVD) device, the chamber pressure is adjusted to be stable at 3.0 kPa, the power is 400 W, and the hydrogen flow rate is 200 sccm. After processing for 15 minutes, the power is reduced to 0 at a rate of 0.5 V / min in a hydrogen atmosphere to complete the Ta deposition process.

[0054] (3) placing the graphite sheet treated in step (2) into a quartz tube and sealing the tube, evacuating the quartz tube while sealing the tube to ensure that the quartz tube is in a near-vacuum state, placing the sealed quartz tube (with the sample inside) into a muffle furnace at 1100° C., taking out the sample after annealing for 30 minutes, and completing the annealing process.

[0055] Field emission scanning electron microscopy (FESEM) and high resolution transmission electron microscopy (HRTEM) were used to observe the composition of the samples after the experiment.

[0056] Figure 7 This is the SEM picture of Example 3. After annealing, dense spherical nanoparticles exist on the surface of the sample. Compared with the Ta wire treatment at a pressure of 2.5 kPa (Example 2), the size of the nanoparticles on the surface of the sample becomes smaller and the number becomes more.

[0057] Figure 8 This is the TEM image of Example 3. From the low-magnification image (a), it can be seen that there are many nano-spherical particles in the thin area of ​​the sample. SAED-a mainly contains diffraction rings of the (100), (110) and (201) crystal planes of graphite. Figure (b) is an enlarged view of area b in Figure (a), and the corresponding FT image FT-b shows the diffraction information of the crystal plane with a spacing of 0.208nm. From the enlarged image b-1 of the particle, it can be seen that there are clear lattice fringes inside the particle, and the crystal plane spacing is 0.208nm, which is the (111) plane of diamond. The previous analysis shows that diamond particles with a size of about 30nm were obtained in the sample. Compared with the 5-15nm diamonds obtained in the previous patent, the diamond size obtained in this patent is larger.

[0058] Example 4

[0059] (1) Single crystal flake graphite powder (particle size of 5 μm) was placed in a tablet press (manufactured by Tianjin Botian Shengda Technology Development Co., Ltd., model FW-4A, pressed at a pressure of 30 MPa for 2 min) and pressed into graphite sheets. The surface of the graphite sheet was cleaned with an ethanol solution, and the surface was dried by a nitrogen gun to prepare a graphite sheet.

[0060] (2) The tantalum wire is tooled in the form of a double spiral. The graphite sheet prepared in step (1) is placed in a hot wire chemical vapor deposition (HFCVD) device, the chamber pressure is adjusted to be stable at 2.5 kPa, the power is 400 W, and the hydrogen flow rate is 200 sccm. After processing for 15 minutes, the power is reduced to 0 at a rate of 0.5 V / min in a hydrogen atmosphere to complete the Ta deposition process.

[0061] (3) placing the graphite sheet treated in step (2) into a quartz tube and sealing the tube, evacuating the quartz tube while sealing the tube to ensure that the quartz tube is in a near-vacuum state, placing the sealed quartz tube (with the sample inside) into a muffle furnace at 700° C., taking out the sample after annealing for 30 minutes, and completing the annealing process.

[0062] Field emission scanning electron microscopy (FESEM) and high resolution transmission electron microscopy (HRTEM) were used to observe the composition of the samples after the experiment.

[0063] Fig. 9This is the SEM picture of Example 4. After annealing, no obvious nanoparticles appear on the surface of the sample. Compared with the annealing temperature of 1100° C. (Example 2), the number of surface particles decreases significantly.

[0064] Fig.10 This is the TEM image of Example 4. From the low-magnification image (a), it can be seen that the thin area of ​​the sample is mainly graphite, and there are a large number of amorphous areas in the graphite. SAED-a mainly contains diffraction rings of the (100), (110) and (201) crystal planes of graphite, and diffraction points of the (111) crystal plane of diamond. Figure (c) is an enlarged view of area b in Figure (a), and the corresponding FT image FT-b shows the diffraction information of crystal planes with spacings of 0.207nm and 0.103nm. From the enlarged image c-1 of the particle, it can be seen that there are lattice fringes with a crystal plane spacing of 0.207nm inside the particle, which is consistent with the crystal plane spacing of the cubic diamond (111) plane. The previous analysis shows that diamond particles with a size of about 17nm were obtained in the sample, which is larger than the diamond size (5~15nm) obtained in the previous patent.

[0065] Example 5

[0066] (1) Single crystal flake graphite powder (particle size of 5 μm) was placed in a tablet press (manufactured by Tianjin Botian Shengda Technology Development Co., Ltd., model FW-4A, pressed at a pressure of 30 MPa for 2 min) and pressed into graphite sheets. The surface of the graphite sheet was cleaned with an ethanol solution, and the surface was dried by a nitrogen gun to prepare a graphite sheet.

[0067] (2) The tantalum wire is tooled in the form of a double spiral. The graphite sheet prepared in step (1) is placed in a hot wire chemical vapor deposition (HFCVD) device, the chamber pressure is adjusted to be stable at 2.5 kPa, the power is 400 W, and the hydrogen flow rate is 200 sccm. After processing for 15 minutes, the power is reduced to 0 at a rate of 0.5 V / min in a hydrogen atmosphere to complete the Ta deposition process.

[0068] (3) placing the graphite sheet treated in step (2) into a quartz tube and sealing the tube, evacuating the quartz tube while sealing the tube to ensure that the quartz tube is in a near-vacuum state, placing the sealed quartz tube (with the sample inside) into a muffle furnace at 900° C., taking out the sample after annealing for 30 minutes, and completing the annealing process.

[0069] Field emission scanning electron microscopy (FESEM) and high resolution transmission electron microscopy (HRTEM) were used to observe the composition of the samples after the experiment.

[0070] Fig.11This is the SEM picture of Example 5. After annealing, a small amount of nanoparticles appear on the surface of the sample. Compared with the annealing temperature of 700°C (Example 4), the number of surface particles has increased significantly, but the number of nanoparticles is not as dense as the annealing temperature of 1100°C (Example 2).

[0071] Fig.12 This is the TEM image of Example 5. From the low-magnification image (a), it can be seen that there are a small number of nanoparticles on the thin area of ​​the sample. Most of these nanoparticles are amorphous carbon balls, and there are a few tantalum particles. SAED-a mainly contains diffraction rings of the (100), (110), and (201) crystal planes of graphite and diffraction information of the (410) and (221) crystal planes of tantalum. Figure (c) is an enlarged view of the c area in Figure (b). The corresponding FT image FT-c shows the diffraction information of crystal planes with spacings of 0.210nm and 0.213nm. They correspond to the diamond (111) and graphite (100) crystal planes, respectively. From the particle enlargement image c-1, it can be seen that there are lattice fringes with a crystal plane spacing of 0.210nm inside the particles, which are diamond (111) crystal planes. The previous analysis shows that diamond particles with a size of about 19nm were obtained in the sample. Compared with the 5-15nm diamonds obtained in the previous patent, the diamond size obtained in this patent is larger.

[0072] Comparative Example 1

[0073] (1) A graphite sheet (prepared by Beijing Electric Carbon Factory, with a purity of 99.9%) is ground (using 2000 mesh and 4000 mesh sandpaper successively) and polished (using a polishing flannel cloth), ultrasonically cleaned (manufactured by Kunshan Ultrasonic Instrument Co., Ltd., model KQ5200DE, 100W-200W ultrasonic for 15 minutes, preferably 140W) in an organic solvent (ethanol or acetone can be selected, preferably ethanol), cleaned with deionized water, and dried (dried with a nitrogen gun) to obtain a pretreated polycrystalline graphite sheet; the above pretreatment is to obtain a polycrystalline graphite sheet with a smooth and clean surface.

[0074] (2) The tantalum wire is tooled in the form of a double spiral. The graphite sheet prepared in step (1) is placed in a hot wire chemical vapor deposition (HFCVD) device, the chamber pressure is adjusted to be stable at 3.0 kPa, the power is 400 W, and the hydrogen flow rate is 200 sccm. After processing for 15 minutes, the power is reduced to 0 at a rate of 0.5 V / min in a hydrogen atmosphere to complete the Ta deposition process.

[0075] (3) placing the graphite sheet treated in step (2) into a quartz tube and sealing the tube, evacuating the quartz tube while sealing the tube to ensure that the quartz tube is in a near-vacuum state, placing the sealed quartz tube (with the sample inside) into a muffle furnace at 1100° C., taking out the sample after annealing for 30 minutes, and completing the annealing process.

[0076] Field emission scanning electron microscopy (FESEM) and high resolution transmission electron microscopy (HRTEM) were used to observe the composition of the samples after the experiment.

[0077] Fig.13 This is the SEM picture of comparative example 1. After annealing, a large number of nanoparticles appear on the surface of the sample. Compared with the single crystal flake graphite substrate (Example 3), the number of surface particles is significantly reduced and the particle size is significantly larger.

[0078] Fig.14 This is the TEM image of Comparative Example 1. From the low-magnification image (a), it can be seen that there are many nanoparticles on the thin area of ​​the sample. Most of the larger nanoparticles are amorphous carbon balls, and most of the smaller nanoparticles are TaC particles with a few diamond particles. SAED-a mainly contains the (100), (110), and (201) crystal plane diffraction information of graphite. Figure (c) is an enlarged view of the c area in Figure (b). From the particle enlarged view (c), it can be seen that there are lattice fringes with a crystal plane spacing of 0.206nm inside the particles, which are diamond (111) crystal planes. The previous analysis shows that diamond particles with a size of about 9nm are obtained in the sample, while diamond particles with a size of about 30nm can be obtained using single-crystal flake graphite, indicating that single-crystal flake graphite as a substrate is more conducive to the transformation of graphite to diamond, and larger diamonds are obtained.

Claims

1. A method for converting graphite into diamond, characterized in that: The method comprises the following steps: S1: In a hot wire chemical vapor deposition device, a tantalum wire tooling is used, a single crystal flake graphite sheet is placed in the cavity of the hot wire chemical vapor deposition device for tantalum deposition, and a graphite sheet treated with tantalum wire is obtained; The tantalum deposition operation is: processing for 5 to 30 minutes under the conditions of a chamber pressure of 2.0 to 3.0 kPa, a hot wire power of 300 to 800 W, and a hydrogen flow rate of 50 to 300 sccm, and then reducing the power to 0 at a rate of 0.2 to 2 V / min in a hydrogen atmosphere; S2: The graphite sheet treated with the tantalum wire described in step S1 is sealed in a vacuum quartz tube and annealed in a muffle furnace at 700-1100° C. for 15-120 min to obtain diamond on the graphite sheet.

2. The method for converting graphite into diamond as claimed in claim 1, characterized in that: The single crystal flake graphite sheet is made by pressing single crystal flake graphite powder into sheets.

3. The method for converting graphite into diamond as claimed in claim 2, characterized in that: The tabletting pressure is 30 MPa and the time is 2 min.

4. The method for converting graphite into diamond according to claim 1, characterized in that: The air pressure in the cavity is 3.0 kPa.

5. The method for converting graphite into diamond according to claim 1, characterized in that: The power of the heating wire is 400W.

6. The method for converting graphite into diamond according to claim 1, characterized in that: The flow rate of the hydrogen gas is 200 sccm.

7. The method for converting graphite into diamond according to claim 1, characterized in that: The treatment time is 15 min.

8. The method for converting graphite into diamond according to claim 1, characterized in that: The hot wire chemical vapor deposition equipment described in step S1 was purchased from Shanghai Jiaoyou Diamond Coating Company, model number JUHFCVD001.

9. The method for converting graphite into diamond according to claim 1, characterized in that: The annealing temperature in step S2 is 900° C. and the annealing time is 30 min.

10. The method for converting graphite into diamond according to claim 1, characterized in that The method is: S1: In a hot wire chemical vapor deposition device, a tantalum wire tooling is used, a single crystal flake graphite sheet is placed in the cavity of the hot wire chemical vapor deposition device for tantalum deposition, and a graphite sheet treated with tantalum wire is obtained; The tantalum deposition operation is: processing for 15 min under the conditions of chamber pressure of 3.0 kPa, hot wire power of 400 W, and hydrogen flow rate of 200 sccm, and then reducing the power to 0 at a rate of 0.5 V / min in a hydrogen atmosphere; S2: The graphite sheet treated with the tantalum wire described in step S1 is sealed in a vacuum quartz tube and annealed in a muffle furnace at 900° C. for 30 min to obtain diamond on the graphite sheet.

Citation Information

Patent Citations

  • A method for preparing diamond based on graphite under low pressure

    CN114751408B

  • Method for preparing diamond based on graphite under normal pressure

    CN116282002A

  • Method for preparing nano-diamond based on graphene vertical lamellas

    CN116752114A